The Role of Aerobic Exercise to Prevent Coronary Artery Disease - Damayanti Tinduh; Felisita Maritza Abidanovanty; Nabila Sayyida Fairuz Zen; Fadhilah Rahmaputri (Universitas Airlangga, 2022)
Abstract: Background: Coronary Artery Disease (CAD) is a disorder of heart function caused by blockage or narrowing of the coronary arteries so that there is an insufficiency of blood and oxygen flow to the myocardium and becomes the leading cause of death in the world. CAD is one of the causes of the decline in the quality of life of a human being. Methods: This study used a literature review method using 11 scientific articles as online data sources which were then further analyzed. Result and Discussion: Exercise is a recommended therapy as half of the pharmacotherapy. Moderate intensity exercise of 150 minutes per week and vigorous-intensity of more than 75 minutes per week greatly help CR also provide significant benefits when started within 15 days of cardiovascular symptoms appearing. Conclussion: CAD causes the most deaths in the world. From various scientific articles that have been analyzed, exercise, especially aerobic exercise, has been shown to have a good impact on people with CAD that affect lipid metabolism, heart remodeling, insulin resistance, and endothelial function.